Prevalence of familial hypercholesterolemia in Attica region, Greece - Pavlatou, Niki; Rovina, Nikoletta; Toylia, Georgia; Kadda, Olga; Marvaki, Christina; Kapadochos, Theodore; Kolovou, Genovefa; Koutsoukou, Antonia (Health & Research Journal, 2021)
Background: Dyslipidemias are one of the major modifiable risk factors for cardiovascular disease. Familial hypercholesterolemia (FH) is the most common genetic metabolic disorder; it is estimated that around 14-34 million people worldwide have FH but only 25% of FH patients have been diagnosed. Aim: The aim of the present study was to explore the prevalence of FH in Attica region, Greece. Methods: Attica region was divided into 8 regional units. A predesigned questionnaire was used to collect demographic and clinical data. Data analysis was performed by using the Statistical Package for the Social Sciences (SPSS), ver. 20. Results: The studied sample consisted of 1578 Greek inhabitants of Attica region. The majority of the sample was women (59.9%). The mean age of the studied participants was 47.1 (±14.9) years. According to Simon Broome criteria, the probability of an FH diagnosis as unlikely is determined in 98.7% of the studied sample, probable in 0.8% of the participants or definite in 0.5% of the participants, based on this data, the prevalence of FH in Attica region, Greece is 1:200. Qualitative factors found to be associated with the onset of the disease were medication (p-value = 0.001) and hypolipidemic therapy (p-value = 0.001). The quantitative factors found to be associated with disease onset were body mass index (p-value = 0.044), and systolic (p-value = 0.001) and diastolic (p-value = 0.007) pressure. Conclusions: Based on our data, the prevalence of FH in Attica region, Greece is 1:200. Early identification of contributing factors in FH development and proper treatment is vital and reduce the risk of premature and severe atherosclerotic disease.